"What other choices might I have made?": Sexual Minority Men, the PrEP Cascade and the Shifting Subjective Dimensions of HIV Risk. (July 2022) - Gaspar, Mark; Wells, Alex; Hull, Mark; Tan, Darrell H. S.; Lachowsky, Nathan; Grace, Daniel
The PrEP Cascade is a dominant framework for investigating barriers to HIV pre-exposure prophylaxis (PrEP), an HIV prevention tool. We interviewed 37 PrEP users and 8 non-PrEP users in Ontario and British Columbia, Canada, about their decision-making through the Cascade. Participants were HIV-negative gay, bisexual, and queer men (GBQM). The data were analyzed using thematic analysis. PrEP decision-making was based on pragmatic considerations (logistics, costs, and systemic barriers), biomedical considerations (efficacy, side-effects, and sexually transmitted infections), and subjective considerations (identity, politics, and changing sexual preferences). Affective attachments to established versions of "safer sex" (condoms and serosorting) made some GBQM less likely to try PrEP. Some GBQM expressed increased social expectations to use PrEP, have condomless sex, and serodifferent sex. These findings support offering PrEP at no-cost, offering individualized counseling and community-based opportunities to discuss PrEP use and changing sexual practices, and improving communication on the manageability of PrEP side-effects.